INFLUENCE OF LEAF AGE ON FEEDING AND FOOD UTILIZATION IN ORTHACRIS MAINDRONI (WINGLESS GRASSHOPPER) (ORTHOPTERA : ACRIDIDAE) - MURUGAN, K.; SENTHAMILSELVI, S.; CHITRA, T. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1992)
Nutritional influence of Tephrosia purpurea on Orthacris maindroni was studied. Significant differences were observed in the feeding and food utilization of the grasshoppers depending upon the age of leaves utilized as well as its biochemical profiles particularly protein, carbohydrates and lipids. Insects fed on mature leaves showed better food utilization efficiency than the otherleaf stages.